2022
DOI: 10.13075/mp.5893.01229
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor modulation and bladder cancer prevention – a short review

Abstract: The prevalence of bladder cancer (BCa) is 4 times higher in men as compared to women, and gender differences have been the focus of attention for few years. Androgen receptor (AR) may be a putative explanation for gender differences. It may also be related to unfavourable BCa progression and development because of the increased androgen sensitivity of urothelium to carcinogens. Moreover, cigarette smoking and occupational exposure to carcinogens have been reported to play contributory roles with the highest at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 90 publications
(124 reference statements)
0
2
0
Order By: Relevance
“…Bladder cancer incidence is increasing nowadays due to occupational and environmental exposure. Exposure to heavy metal is reported to play contributory roles with increasing risk of BC [ 21 ]. Our study was conducted on 49 BC patient varying in their grades and stage in Urology and Nephrology Center, Mansoura University.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder cancer incidence is increasing nowadays due to occupational and environmental exposure. Exposure to heavy metal is reported to play contributory roles with increasing risk of BC [ 21 ]. Our study was conducted on 49 BC patient varying in their grades and stage in Urology and Nephrology Center, Mansoura University.…”
Section: Discussionmentioning
confidence: 99%
“…The initiation and progression of bladder cancer (BCa) may be tightly related to the androgen receptor (AR). 111 After analyzing BCa survival based on TCGA database, it was found that PD-L1 expression negatively correlated to survival in male BCa patients but not in female patients. Thus, AR has been speculated to regulate PD-L1 expression.…”
Section: Hsa_circ_0046523mentioning
confidence: 99%